2018
DOI: 10.1002/elan.201700839
|View full text |Cite
|
Sign up to set email alerts
|

N‐Doped Hollow Porous Carbon Spheres/Bismuth Hybrid Film Modified Electrodes for Sensitive Voltammetric Determination of Trace Cadmium

Abstract: In this work, N‐doped hollow porous carbon spheres (N‐HPCSs) were synthesized by silicon dioxide template‐assisted polybenzoxazine (PB) coating strategy. The prepared N‐HPCSs have a smooth hollow ball structure surrounded by a well‐defined porous shell. Combining with in‐situ plating of Bi film, the N‐HPCSs were further fabricated a sensitive electrochemical platform for determination trace levels of Cd(II) by differential pulse anodic stripping voltammetry (DPASV). Under the optimized conditions, the Bi‐N‐HPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The phenomenon is potentially because the AAs undergo a rapid adsorption process on the modified electrode within seconds. Subsequently, peak currents increase linearly with accumulation time up to 100 s. When the accumulation time is further extended, the value of peak current moves towards a platform due to the saturation of AAs on the modified electrode . Therefore, the obtained peak current versus time plot demonstrates that the optimal enrichment time is 100 s.…”
Section: Resultsmentioning
confidence: 80%
“…The phenomenon is potentially because the AAs undergo a rapid adsorption process on the modified electrode within seconds. Subsequently, peak currents increase linearly with accumulation time up to 100 s. When the accumulation time is further extended, the value of peak current moves towards a platform due to the saturation of AAs on the modified electrode . Therefore, the obtained peak current versus time plot demonstrates that the optimal enrichment time is 100 s.…”
Section: Resultsmentioning
confidence: 80%
“…Several previous interesting literatures have indicated the doping materials with N can enhance dramatically the related performance, possessing broad application prospects. [40][41][42][43][44] In this work, N-doped HNS loaded with gold nanoparticles (NHNS/ Au) nanocomposite was synthesized firstly and then it was applied to modify electrode to assemble a novel, simple and label-free electrochemical immunosensor of AFP (Scheme 1). The Au particles cannot only improve the sensing performances, but also offer supporting platform for immobilizing AFP antibody (Ab) since Ab can be assembled on the modified [6,45] ).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous interesting literatures have indicated the doping materials with N can enhance dramatically the related performance, possessing broad application prospects [40–44] . In this work, N‐doped HNS loaded with gold nanoparticles (NHNS/Au) nanocomposite was synthesized firstly and then it was applied to modify electrode to assemble a novel, simple and label‐free electrochemical immunosensor of AFP (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have demonstrated that N-doped carbon nanomaterials can obviously enhance the material performance and exhibit extensive application prospects. [26][27][28][29][30] Herein, for achieving highly sensitive and simple determination of CEA, N-doped HMN decorated with nanogold particles (NHMN/Au) hybrids were synthesized firstly via a simple method, and then it was used as sensing platform to immobilize Ab1 for capturing CEA target. The excellent physical/chemical properties (e.g.…”
Section: Introductionmentioning
confidence: 99%